Surgical treatment of gastric and small bowel gastrointestinal stromal tumours - Lukáš Sákra; Jiří Šiller; Petr Vyhnálek; Marie Hácová (Videosurgery and Other Miniinvasive Techniques)
Aim: This study aimed to evaluate a set of gastrointestinal stromal tumours (GIST) of the stomach and the small bowelmanaged with a laparoscopic technique.Material and methods: The study covers a period from January 1, 2007 until June 1, 2010 during which 13 patientsunderwent the laparoscopic removal of stomach tumours and 2 patients underwent the removal of a small bowelGIST in the General Hospital in Pardubice. In all cases tumours were removed in a laparoscopic way, including thehealthy border of the stomach tissue.Results: No death was observed in our study. Two patients suffered from wound infection (secondary healing), one ofthem requiring repeat surgery owing to the excessive narrowing of the distal part of the stomach. Dehiscence oflaparoscopic sutures or other intra-abdominal complications were not observed. During monitoring all patients werefree of signs of local recurrence, but tumour progression into the liver was observed in 1 patient. Gastrointestinal stromaltumours are very rare tumours but their incidence is increasing. At this time the consensus about the necessity ofpreoperative unambiguous differentiation between malignant or less malignant variants is not available. Strict differentiationis very difficult and the decision whether to choose a more radical surgical approach for more malignantvariants is not clear-cut.Conclusions: In cases of gastric and small bowel GISTs the local removal of a tumour with the healthy border of thestomach tissue may be chosen as an adequate approach. Our results support this local surgical approach.